The Galician Audio-visual Sector in fiction Literature - González Rodríguez, Xurxo (Madrygal. Revista de Estudios Gallegos, 2004)
This article aims at tracing the evolution of the Galician audio-visual sector by analising a number of fiction works, in which, either directly or reportedly, story-writers and image-shapers (in this case in the realm of literature) render their reflections upon the feebleness of the Galician audio-visual discourse. Audio-visual, cinema, Galicia, fiction, intertextuality, witness, history.